2013
DOI: 10.1002/er.3112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnetic field and pulse potential on hydrogen production via water electrolysis

Abstract: SUMMARY This experiment uses nickel electrodes and adds pulse potential and magnetic force when producing hydrogen via water electrolysis and explores how related parameters are affected by magnetohydrodynamics and pulse potential. Experiments showed that the Lorentz force of the magnetic field changes the direction of convective flow of the electrolyte, which affects the flow of bubbles during electrolysis. Adding a magnetic field increases the rate of current density by roughly 15% under a normal temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…The magnetic noble metal nanocomposite system has been established to study the role of Lorentz force in electrocatalysis according to previous literatures . Lorentz force was found to make a difference to the redox process of water electrolysis, tuning the electron transfer rate . Inspired from aforementioned works, we designed rationally a multifunctional nanocomposite used as ORR electrocatalyst, possessing magnetic core and defective carbon shell with Pd NPs embedded.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic noble metal nanocomposite system has been established to study the role of Lorentz force in electrocatalysis according to previous literatures . Lorentz force was found to make a difference to the redox process of water electrolysis, tuning the electron transfer rate . Inspired from aforementioned works, we designed rationally a multifunctional nanocomposite used as ORR electrocatalyst, possessing magnetic core and defective carbon shell with Pd NPs embedded.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is found that the magnetic field has an effect on the bubble dimensions. Lin et al [35] used a Charge Coupled Device (CCD) camera to observe Lorentz Force effect on the oxygen and hydrogen evolution reactions at the electrodes. They concluded that applying a magnetic field results in smaller bubble diameter and found that moving low diameter bubbles off the electrode surface is easier than larger bubbles.…”
Section: Lorentz Force Theory In Pem Water Electrolysersmentioning
confidence: 99%
“…Here, the ferromagnetic nickel electrodes obtained 14.6 % current density improvement. In another study, Lin et al [35] reported that both the magnetic field and the pulse potential remarkably increased hydrogen production efficiency. According to their findings, by the help of pulse potential, bubble removal acceleration and mass transfer ratio is enhanced.…”
Section: Introductionmentioning
confidence: 97%
“…Lin investigated the effect of a magnetic field and pulsed potential on hydrogen evolution using nickel electrodes [104]. They showed that the Lorentz force of the magnetic field changes the direction of convective flow of the electrolyte and, that generally a pulsed potential and magnetic field simultaneously enhance hydrogen evolution performance.…”
Section: Hydrogen Generationmentioning
confidence: 99%